Resistensi Flukonazol pada Candida glabrata: Mekanisme Molekuler Mutasi Gen ERG11 - Astri Arri Febrianti; Robiatul Adawiyah; Ratika Rahmasari (Jurnal Ilmu Kedokteran, 2026)
Candida glabrata is one of the leading causes of non-albicans Candida infections with an increasing prevalence worldwide. This species is associated with high mortality rates and a marked tendency to develop resistance to antifungal agents, particularly azoles such as fluconazole. A comprehensive understanding of its biological characteristics, pathogenic mechanisms, and resistance patterns is essential for improving diagnosis and therapeutic strategies. The genetic factor that plays an important role in this resistance mechanism is the ERG11 gene, which encodes the lanosterol 14-α-demethylase enzyme, the main target of fluconazole in the ergosterol biosynthesis pathway. This review was conducted based on an analysis of recent literature focusing on the biology, epidemiology, pathogenesis, antifungal resistance mechanisms, susceptibility testing methods, and molecular identification of Candida glabrata. Special emphasis was given to the role of the ERG11 gene in fluconazole resistance and the application of molecular tools such as ITS and D1/D2 rDNA sequencing for species-level identification. The findings indicate that Candida glabrata exhibits several virulence factors, including adhesins, biofilm formation, cell wall modifications, and iron acquisition strategies. Antifungal resistance is mediated through mutations in the ERG11 gene, overexpression of efflux pumps (CgCDR1, CgCDR2, CgSNQ2), alterations in sterol biosynthesis pathways, and mitochondrial dysfunction (petite mutants). Susceptibility testing methods following CLSI/EUCAST standards, as well as automated systems such as VITEK 2, have shown reliable and rapid results. Candida glabrata is an emerging pathogen with rising prevalence and complex antifungal resistance mechanisms. Accurate species identification and molecular analysis of the ERG11 gene are crucial for understanding local resistance patterns and supporting the development of more effective therapeutic strategies.